FDI and the relevance of spatial linkages: do third country effects matter for Dutch FDI? - Harry Garretsen; Jolanda Peeters (Center for Economic Studies and ifo Institute (CESifo), 2008)
The aim of this paper is to test for the relevance of spatial linkages for Dutch (outbound) FDI. To do so, and based on recent FDI theories, we estimate a spatial lag model to assess the importance of spatial linkages for Dutch FDI to 18 host countries. As a determinant of FDI, space or geography also enters our empirical analysis through the market size and a corporate income tax variable. Our paper is among the few to date to take spatial linkages with respect to FDI into account. The Dutch case is also interesting because Dutch firms account for a large part of global FDI and related research has so far focused mainly on US FDI. After controlling for fixed effects, we find for our sample period 1984-2004 that third country effects matter, but the results are somewhat sensitive to sample and model selection. Apart from our benchmark spatial lag model, we discuss and estimate various alternative models notably by looking at European host FDI countries only, by dividing FDI into industry and services FDI and by estimating a spatial error model as well.
Keywords: F20; 330; Direktinvestition; Niederländisch; Makroökonomischer Einfluss; Welt; Außenhandelseffekt; Niederlande